Saint Methodius: Life and Canonization - Láleva, Tania Dimitrova (Studia Ceranea, 2019)
The article discussed the time and place of the canonization of Methodius and the difference in the treatment he received in the Roman Catholic Church and in the Bulgarian Church. The study highlights the overall distinct treatment of the two brothers while tracing the changes in the attitude to Methodius as opposed to that to Cyril in the first texts written in the Slavonic alphabet, in Bulgaria. Two canons and anonymous stichera from the service on the feast day of Methodius indicate that his disciples played a significant role for establishing the cult of Methodius. In the earlier years, there was a difference – the cult of Methodius was in the process of establishment, while Cyril had already been recognized as a saint whose cult was supported by an established tradition and whose figure had been used to support the holiness of his elder brother, later born to eternal life. The study also determines the time of the beginning of the cult of Methodius in Bulgaria at the end of the 9th and the beginning of the 10th century, after the treatise On the Letters and after the translation of the Nebesa (“Heaven”) by John the Exarch in Old Bulgarian, most likely at the time of Constantine of Preslav and Clement of Ochrid.